Textual Study of the Work "Decipher of Fest of Human Virtual-Celebration of Newborn” - Munkhbat, Turmandakh (Tibetan Studies, 2025)
Mongolian scholar-monks not only translated Sanskrit and Tibetan texts, sutras, and literary works into Mongolian, thereby disseminating Buddhist literature, philosophy, and teachings to the Mongolian people, but they also composed scholarly works in the Tibetan language, influencing Tibetan religion and culture. This indicates that Mongolian scholar-monks had an advanced proficiency in the Tibetan language. The "The Fest of human ritual,” authored by the renowned Mongolian scholar Alxa Agvaandandar Lharamba (1759-1840), uses a significant number of archaic terms of Tibetan, synonyms, honorific terms, and regional dialects, making its terminology rare and complex. As a result, it was considered a core literary text within the traditional Mongolian Ih Khuree curriculum, specifically the "Ten Minor literary" compilation, which taught translation from Tibetan into Mongolian. Over generations, scholars have studied this work and created numerous commentaries and translations, including "brda bkrol" (decipher of terms) and "btus ming" (collection of terms), which serve as glossaries for the difficult terms in the text. Among these commentaries, "Decipher of Fest of Human Virtual-Celebration of newborn" (tib: blabs bya mi chos dga' ston gyi brda' bkrol byis ba’i rol rdzod) by Lodan is particularly intriguing. The author of this commentary, Lodan (tib: blo ldan), remains biographically elusive. However, through "Decipher of Fest of Human Virtual-Celebration of newborn", we aim to clarify certain details related to his life by drawing upon his commentary. Furthermore, we present the bibliographic sources used to explicate approximately 600 difficult words within the main work and words that have been translated into Mongolian and Chinese using Tibetan transliteration. “Хүмүүний номын баяр хуримын дохионы тайлбар нялхсын хөг найр” зохиолын бичвэр зүйн судалгаа Хураангуй: Монголын эрдэмтэн лам нар санскрит, төвөд хэлт ном судрыг монгол хэлэнд орчуулан, Бурханы шашны утга зохиол, гүн ухаан, сургаалын зохиол бүтээлүүдийг түгээн дэлгэрүүлэхийн зэрэгцээ төвөд хэлээр ном зохиол туурвин төвөдийн шашин, соёлд харилцан нөлөөлж ирсэн зэргээс үзвэл монголын эрдэмтэн, лам нар төвөд хэлийг ахисан түвшинд суралцдаг байсан нь тодорхой байна. Монголын нэрт эрдэмтэн Алшаа Агваандандар лхаарамбын (1759-1840) туурвисан “Хүмүүний номын баяр хурим” зохиол нь Төвөд хэлний хуучин үг хэллэг, илт өгүүлэх нэр, хүндэтгэлийн нэр болон нутгийн үг хэллэг зэрэг нэр томьёог түлхүү ашигласан нь их хүрээний уламжлалт нэр орчуулгын хичээл буюу төвөд хэлнээс монгол хэлэнд орчуулгын хичээлд “Нэрийн арван бага” эмхэтгэлийн голлох бүтээл болгон судалдаг байжээ. Энэ бүтээлийг үе үеийн эрдэмтэн мэргэд судалж, уг зохиолын бэрх үгийн тайлбар болсон дохионы тайлбар (тө: brda bkrol), түүвэр нэр (тө: btus ming), орчуулга зэрэг олон тайлбар зохион туурвисны дотроос “Хүмүүний номын баяр хуримын дохионы тайлбар нялхсын хөг найр” (тө: blabs bya mi chos dga’ ston gyi brda’ bkrol byis ba’i rol rdzod) сонирхол татна. Уг тайлбарын зохиогч Лоданы (тө: blo ldan) намтар тодорхойгүй боловч бид энэхүү ажлаараа түүний намтартай холбоотой зарим мэдээг “Хүмүүний номын баяр хуримын дохионы тайлбар нялхсын хөг найр” нэрт дохионы тайлбараас тодруулах, “Хүмүүний номын баяр хурим” зохиолын 600 орчим бэрх үгийг тайлбарлахдаа ашигласан эшлэл, ном зүй болон зарим үгийг Монгол, Хятад хэлэнд орчуулж төвөд үсгээр галиглан бичсэн зэргийг танилцуулж байна. Түлхүүр үг: Дохионы тайлбар, Алшаа Агваандандар лхаарамба, Хүмүүний номын баяр хурим, Лодан